Optimizing gross motor skills in elementary school students through the traditional game gobak sodor - Arifin, Bustanol; Muzakki, Abdurrohman; Suwandayani, Beti Istanti (Universitas Negeri Surabaya, 2025)
This study aims to analyze the effectiveness of the traditional game Gobak Sodor as a medium for developing gross motor skills in elementary school students physical education. The research employed a true experimental pretest–posttest control group design involving 40 children aged 7–9 years from SD Nusantara Jakarta Timur. Participants were randomly assigned to an experimental group, which participated in structured Gobak Sodor sessions twice a week for four weeks, and a control group, which performed conventional physical education activities. The gross motor observation sheet served as the instrument to assess strength, agility, balance, and coordination. Data from pretests and posttests were analyzed using paired sample t-tests and independent sample t-tests via SPSS version 25, with a significance level of 0.05. The results indicated a significant improvement in the experimental group (mean score increased from 15.22 to 76.11) compared with the control group (12.17 to 62.67), with p = 0.003. These findings confirm that Gobak Sodor positively influences gross motor skill enhancement in elementary school students, while also promoting social interaction and cultural appreciation through play-based learning. The study’s limitations include a short intervention period and a relatively small sample size. Future research should involve larger samples and explore other traditional games to enhance generalizability and deepen understanding of culturally grounded physical education strategies.